In vitro studies on phytochemical analysis and antioxidant activity of Manilkara zapota (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Sapota is one of the prominent fruits and belongs to family sapotaceae. India is the largest producer of sapota. In this present study, phytochemicals were analysed and antioxidant activity was determined for sapota fruit. The antioxidant capacity of the Manilkara zapota  L fruit extract was evaluated by three different in vitro methods: DPPH activity, hydrogen  peroxide scavenging activity and total antioxidant activity. The ethanolic extract showed best antioxidant activity almost equal to that of standard ascorbic acid. The antioxidant capacity of ethanolic extract may be due to its high phytochemical constituents. The high antioxidant capacity observed in aqueous and ethanolic extracts suggested that this plant could be used as an additive in the food industry providing good protection against oxidative damage. Results indicate that nutrient composition, phytochemical and antioxidant activity of sapota was promising. It is also a good source of antioxidants. These antioxidants are important in all of our diets, especially in infant diets. Thus sapota fruit can be used as a potent therapeutic agent.